Impact of zinc oxide nanoparticles on callus growth, antioxidant activity, and secondary metabolite content in Moringa oleifera - Kalefa, Abdalrahman E.; Salim, Siham A.; Ateya, Nabaa H.; Mahmoud, Huda M. (International Journal of Innovative Research and Scientific Studies, 2025)
This study was carried out in the laboratories of the Biology Department and aims to know the role of 2,4-D and nano-zinc concentrations on callus induction and growth of Moringa oleifera Lam. Its seeds were grown in media containing different concentrations of 2,4-D, and the concentration of 0.75 was chosen as it gave the best callus induction. Then, we made four concentrations of the nano-ZnO compound in addition to the comparative concentration to know their effect on the biomass of callus cultures, the accumulation of some pharmaceutical compounds, and antioxidant activity. Results showed that a maximum callus fresh weight was seen at 10.0 mg.L-1, with a mean weight of 999.74 mg, indicating that this concentration is especially effective at promoting callus growth. The concentration of 25.0 mg.L-1 was found to exhibit the highest level of antioxidant activity, with an IC50 value of 96.78 ± 3.28 mg.L-1. This suggests that this dosage is the most efficient in promoting antioxidant qualities. Results pointed to the potential of Nano-ZnO as a helpful agent in promoting alkaloid and phenolic synthesis in plant tissue culture. Finally, it can be said that stimulation by the nano-ZnO compound leads to an increase in vital biological materials.